Homing endonucleases residing within inteins: evolutionary puzzles awaiting genetic solutions. (19th January 2011) - Barzel, Adi; Naor, Adit; Privman, Eyal; Kupiec, Martin; Gophna, Uri
Abstract : Inteins are selfish genetic elements that disrupt the sequence of protein-coding genes and are excised post-translationally. Most inteins also contain a HEN (homing endonuclease) domain, which is important for their horizontal transmission. The present review focuses on the evolution of inteins and their nested HENs, and highlights several unsolved questions that could benefit from molecular genetic approaches. Such approaches can be well carried out in halophilic archaea, which are naturally intein-rich and have highly developed genetic tools for their study. In particular, the fitness effects of habouring an intein/HEN can be tested in direct competition assays, providing additional insights that will improve current evolutionary models.